A model of hemorrhagic cystitis induced with acrolein in mice - Batista,C.K.L.P. (2006)
Acrolein is a urinary metabolite of cyclophosphamide and ifosfamide, which has been reported to be the causative agent of hemorrhagic cystitis induced by these compounds. A direct cytotoxic effect of acrolein, however, has not yet been demonstrated. In the present study, the effects of intravesical injection of acrolein and mesna, the classical acrolein chemical inhibitor, were evaluated. Male Swiss mice weighing 25 to 35 g (N = 6 per group) received saline or acrolein (25, 75, 225 µg) intravesically 3, 6, 12, and 24 h before sacrifice for evaluation of bladder wet weight, macroscopic and histopathological changes by Gray's criteria, and 3 and 24 h for assessment of increase in vascular permeability. In other animals, mesna was administered intravesically (2 mg) or systemically (80 mg/kg) 1 h before acrolein. Intravesical administration of acrolein induced a dose- and time-dependent increase in vascular permeability and bladder wet weight (within 3 h: 2.2- and 21-fold increases in bladder wet weight and Evans blue dye exuded, respectively, at doses of 75 µg/bladder), as confirmed by Gray's criteria. Pretreatment with mesna (2-mercaptoethanesulfonic acid), which interacts with acrolein resulting in an inactive compound, inhibited all changes induced by acrolein. Our results are the first demonstration that intravesical administration of acrolein induces hemorrhagic cystitis. This model of acrolein-induced hemorrhagic cystitis in mice may be an important tool for the evaluation of the mechanism by which acrolein induces bladder lesion, as well as for investigation of new uroprotective drugs.